Periodic crack-model of comb transducers: excitation of interface waves - DANICKI, E. (Archives of Acoustics, 2000)
A model for a comb transducer is proposed and analyzed. It is shown that interface waves are generated in the comb-sample contact area. The interface waves are leaky waves that transport acoustic energy along the interface towards the comb edges, where it is eventually converted into surface acoustic waves propagating outside the comb. By including piezoelectric effects in the comb and the sample materials, it is possible to analyze the incident bulk wave generated by embedded metal strips on both sides of the interface. Approximations for the scattered wavefield and the relationship describing the energy transfer along the interface are derived. Numerical examples are presented.